Phylogeny and systematics of Old World serotine bats (genus Eptesicus, Vespertilionidae, Chiroptera): an integrative approach. (20th May 2013) - Juste, Javier; Benda, Petr; Garcia‐Mudarra, Juan Luis; Ibáñez, Carlos
Abstract : Integrative taxonomy aims to document biodiversity by incorporating all useful characters to increase confidence in hypotheses about phylogenetic relationships. In this study, we combine data obtained independently from morphology, two maternally inherited mtDNA genes and two biparentally inherited nuDNA genes to make phylogenetic and taxonomic hypotheses about the Palaearctic members of the bat genus Eptesicus (Vespertilionidae). This genus is distributed worldwide (except for Antarctica) and is highly diversified, presenting one of the most entangled taxonomic puzzles among all mammals. Our results support restoring the genus Rhyneptesicus and separating E. isabellinus and E. pachyomus from E. serotinus and E. ognevi and E. anatolicus from E. bottae . Differences in the phylogenetic hypotheses from mtDNA and nuDNA data suggest the occurrence within E. serotinus of evolutionary processes such as mtDNA capture and secondary contacts between partially differentiated ecomorphs. These two evolutionary processes deserve more in‐depth studies within the group.